1996
DOI: 10.1071/ar9960829
|View full text |Cite
|
Sign up to set email alerts
|

Changing perceptions of the effect of plant phenolics on nutrient supply in the ruminant

Abstract: Mammalian metabolism of plant phenolics, initially studied in monogastric animals, gave an emphasis to their toxic and antinutrient effects. Subsequent studies in tropical ruminants and wild herbivores have highlighted the high levels than can occur in some diets and the extensive microbial modification and degradation that can occur in the tract. This paper reviews aspects of plant phenolics as they relate to ruminant nutrition in tropical or semi-arid environments in which some forage plants contain high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 56 publications
2
44
1
Order By: Relevance
“…In contrast, interactions of plant phenolics with proteins may lead to the formation of soluble or insoluble complexes (Shahidi and Naczk 2004). These interactions may have a detrimental effect on the in vivo bioavailability of both phenolics and proteins (Lowry et al 1996;Wollgast and Anklam 2000). Naczk et al (2011) reported that crude extract of phenolics isolated from mangosteen peel displayed a strong protein-precipitating potential.…”
Section: Antioxidant Activity Of Bioactive Compounds From Mangosteen mentioning
confidence: 99%
“…In contrast, interactions of plant phenolics with proteins may lead to the formation of soluble or insoluble complexes (Shahidi and Naczk 2004). These interactions may have a detrimental effect on the in vivo bioavailability of both phenolics and proteins (Lowry et al 1996;Wollgast and Anklam 2000). Naczk et al (2011) reported that crude extract of phenolics isolated from mangosteen peel displayed a strong protein-precipitating potential.…”
Section: Antioxidant Activity Of Bioactive Compounds From Mangosteen mentioning
confidence: 99%
“…These may assist in the detoxification process and also provide additional nutrients to rumen microorganisms, as mulga tannins are known to reduce protein digestibility [91]. The addition of methionine and choline to chick diets alleviated the toxicity of tannic acid and also the toxicity of CTs or possibly the low molecular weight phenolics in sorghum [33], presumably because they functioned as methyl donors in the detoxification process and facilitated the excretion of compounds such as 4-Omethyl gallic acid [35].…”
Section: Supplementationmentioning
confidence: 99%
“…The effect of tannins on GP is through substrate deprivation or enzyme activity inhibition in rumen microbes. The effect of PA on fermentation is more pronounced with PA containing more PD monomeric units (Huyen et al, 2016;Lowry et al, 1996). All PA-containing browse in the present experiment with the exception of D. angustifolia contained PD, indicating that the GP and CH 4 depressing effect partly originated from PD activity.…”
Section: Browse Polyphenol Composition In Relation To Gas and Ch 4 Prmentioning
confidence: 58%
“…Molecular size, solubility and the number of phenolic groups determine complexation formed by hydrogen bonding between the phenolic protons and the peptide carbonyl groups (Lowry et al, 1996). In general, tannins have higher affinity towards large, porous, proline rich proteins and precipitation of proteins is effective at a neutral pH (Hagerman et al, 1992).…”
Section: Biological Activity Of Browse Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation